Enhancing life effectiveness skills: Impacts of length of program in outdoor education camp / Muhammad Wafi A. Rahman … [et al.] - A. Rahman, Muhammad Wafi; Mohd Rasyid, Nelfianty; Hashim, Ahmad; Md Taff, Md Amin; Basal, Mohd Helme; Shafie, Mohd Shariman (Faculty of Sports Science and Recreation, 2017)
The objective of this study was to examine the effects of length of outdoor education program on life effectiveness skills among two public universities students in Malaysia. Life Effectiveness Questionnaire (LEQ-H) was administrated among 256 participants who were chosen as a sample by using purposive sampling. The data were analysed using MANOVA analysis. The result showed that there was a statistically significant difference for overall psychological factor of life effectiveness on length of program for both universities outdoor education program. The implication of the findings provides evidence on the effectiveness duration of outdoor education program in improving students’ life effectiveness. This study provides useful input for Ministry of Higher Education, universities and outdoor. education practitioners. This study also provides an empirical data for future study in this field.